2014
DOI: 10.1016/j.freeradbiomed.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor blockade suppresses light-induced neural damage in the mouse retina

Abstract: Exposure to light contributes to the development and progression of retinal degenerative diseases. However, the mechanisms underlying light-induced tissue damage are not fully understood. Here, we examined the role of angiotensin II type 1 receptor (AT1R) signaling, which is part of the renin-angiotensin system, in light-induced retinal damage. Light-exposed Balb/c mice that were treated with the AT1R blockers (angiotensin II receptor blockers; ARBs) valsartan, losartan, and candesartan before and after the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 69 publications
6
40
0
Order By: Relevance
“…One source of oxidative stress can be light exposure; excessive light induces excessive activation of the visual cycle, which causes photoreceptor cell apoptosis. The role of oxidative stress in the mechanism was supported by previous findings that antioxidants, N-acetyl-L-cysteine (NAC) (Narimatsu et al, 2014) and lutein (Sasaki et al, 2012), can attenuate the apoptosis. Given that AMD is closely related to the condition of the retinal pigment epithelium (RPE) and choroid (Grisanti et al, 1997;Grisanti and Tatar, 2008), the influence of light exposure on the RPE-choroid is important in understanding the underlying mechanism of AMD pathogenesis (Ambati et al, 2003a).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…One source of oxidative stress can be light exposure; excessive light induces excessive activation of the visual cycle, which causes photoreceptor cell apoptosis. The role of oxidative stress in the mechanism was supported by previous findings that antioxidants, N-acetyl-L-cysteine (NAC) (Narimatsu et al, 2014) and lutein (Sasaki et al, 2012), can attenuate the apoptosis. Given that AMD is closely related to the condition of the retinal pigment epithelium (RPE) and choroid (Grisanti et al, 1997;Grisanti and Tatar, 2008), the influence of light exposure on the RPE-choroid is important in understanding the underlying mechanism of AMD pathogenesis (Ambati et al, 2003a).…”
Section: Introductionmentioning
confidence: 75%
“…Because light exposure increases the ROS level in the retina (Narimatsu et al, 2014), we first analyzed whether ROS levels were different in the RPE-choroids of the mice after exposure to light in the box made of clear or yellow IOL material (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we succeeded the induction of the retinal damage by 12 times lower intensity and 6 times shorter hours of blue LED exposure than the previous model. 19,21,22) While several studies reported that NAC protected against light-induced retinal damage, 13,14) no studies exist that that showed its protective effect in an in vivo model of LED light-induced retinal damage. In the present study, NAC was protective against murine blue LED light-induced retinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…13,14) Electroretinogram Electroretinogram (ERG) was recorded on 5 d after blue LED light exposure. Mice were housed in a completely dark room for 24 h, followed by anesthesia with ketamine (120 mg/kg, intraperitoneally (i.p.…”
Section: Animalsmentioning
confidence: 99%
“…However, when ROS levels exceed processing capacity, they cause abnormal modifications of cellular components, such as proteins, and subsequently dysregulate multicellular organelles and induce cellular death [14]. Similarly, excessive light exposure increases ROS generation and causes retinal photoreceptor death [15, 16]. …”
Section: Introductionmentioning
confidence: 99%